CSC463: Fundamentals of Artificial Intelligence / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2017)
The course aims to provide students with basic concepts of artificial intelligence (AI). It will discuss knowledge representation, search strategies, reasoning with uncertainties, and knowledge representation learning. Upon the completion of the course, students should be able to understand the fundamental principles of artificial intelligence concepts, basic approaches of artificial intelligence methods and are able to apply AI techniques to solve complex problems.